First-Principles Study of the Structural Stability and Electronic and Elastic Properties of Helium in α-Zirconium - Jian Zheng; Huijun Zhang; Xiaosong Zhou; Jianhua Liang; Liusi Sheng; Shuming Peng (Advances in Condensed Matter Physics)
First-principles calculations within density functional theory have been performed to investigate the behaviors of helium in α-zirconium. The most favorable interstitial site for He in α-Zr is not an ordinary tetrahedral or octahedral site, but a basal octahedral site with a formation energy as low as 2.40 eV. The formation energy reduces to 1.25 eV in the presence of preexisting vacancies. The analysis on the density of states and the charge density has been carried out. In addition, the influences of He and small He-V complexes on the elastic properties have been studied. The He-V complexes have been found to greatly affect the elastic properties compared with He alone.